THE VEGETATION PERIOD OF SOYBEAN AND THE DEVELOPMENT OF FUNGAL DISEASES (American Journal of Interdisciplinary Research and Development, 2022)
Soybean is one of the main crops in agriculture and currently plays an important role in food security. Also in recent years, great importance has been attached to the cultivation of soybeans in the agro-industrial complex of the republic, from this point of view, one of the factors that seriously affect the yield in soybean cultivation is plant disease during the growing season. The most dangerous soybean diseases are Fusarium (Fusarium L) and Septoria (Septoria glycinis.H). This article describes the growing season of soybean varieties Oyjamol and Tomaris-MMAN and the development of Fusarium (Fusarium L) and Septoria (Septoria glycinis.H) diseases, as well as the effect of seed fertilizers on diseases.